2017
DOI: 10.1590/abd1806-4841.20175241
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, severity and related factors of androgenetic alopecia in dermatology outpatient clinic: hospital-based cross-sectional study in Turkey

Abstract: BACKGROUNDAndrogenetic alopecia (AGA) is a patterned hair loss occurring due to systemic androgen and genetic factors. It is the most common cause of hair loss in both genders. In recent years, many studies investigating the relation between systemic diseases and androgenetic alopecia presented controversial results.OBJECTIVESIn this study we aimed to investigate the frequency of androgenetic alopecia, the presence of accompanying systemic diseases, the relation between body mass index and androgenetic alopeci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 39 publications
9
71
0
Order By: Relevance
“…10 Conversely, some studies have denied any relationship between high BMI or smoking and androgenetic alopecia. 11 The association of hypertension and androgenetic alopecia has also been investigated in several studies, but the results are discrepant. Some studies show a strong relationship between androgenetic alopecia and hypertension, 12 while others fail to show such association.…”
Section: Introductionmentioning
confidence: 99%
“…10 Conversely, some studies have denied any relationship between high BMI or smoking and androgenetic alopecia. 11 The association of hypertension and androgenetic alopecia has also been investigated in several studies, but the results are discrepant. Some studies show a strong relationship between androgenetic alopecia and hypertension, 12 while others fail to show such association.…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, common dermatologic disorders still present unclear points in their physiopathologic characteristics and management . The ability to noninvasively detect the normal morphologic characteristics of the hair and adnexal glands can allow identification of early subclinical abnormalities in many dermatologic conditions that affect millions of people worldwide, such as alopecia and acne …”
mentioning
confidence: 99%
“…detect the normal morphologic characteristics of the hair and adnexal glands can allow identification of early subclinical abnormalities in many dermatologic conditions that affect millions of people worldwide, such as alopecia and acne. 3,4 Hair is a complex and dynamic structure that is one of the main hallmarks of mammals and a distinctive characteristic of an individual. 5 The presence of an excessive amount or its loss can strongly affect self-esteem.…”
mentioning
confidence: 99%
“…6 As a result of numerous factors, mainly androgens and genetic inheritance, along with stress and bad life habits, many young males suffer from AGA with recession of the frontal hairline, which also occurs in older males. 7 Compared with older males, young males have a greater decrease in the quality of life, reduced self-confidence, and if visible, may even have depression. 8 Previous study has always revealed that the cranial hair loss caused older appearance in Western males.…”
Section: Introductionmentioning
confidence: 99%